Incidencias de la falta de conectividad en el proceso de enseñanza aprendizaje de los estudiantes del quinto año de la Escuela de Educación Básica Víctor Hugo - Junco Chávez, Lidia (2024)
This thesis examines the problem of lack of connectivity in the learning process among fifth grade students at the Víctor Hugo Primary School, in the rural sector of Campo Alegre, in the canton of Babahoyo· This educational institution faces a significant lack of connectivity, which affects the effective use of information and communication technologies (ICT) in education· The general objective is to determine the incidents caused by the lack of connectivity in the teaching-learning processes· The methodology used is a mixed research (quali-quantitative), with a correlational-explanatory level and a theoretical, analytical-synthetic and structural-functional method· The study reveals that lack of connectivity and unstable Internet at home and school can have a negative impact on learning· Students face serious limitations in accessing online resources, which creates significant challenges in integrating ICT tools into learning strategies· Despite the difficulties, students recognized the positive impact of the Internet on learning and considered it essential in educational activities· However, the lack of connectivity directly affects the teaching and learning process, perpetuates traditional and obsolete education, thus affecting the quality of education and the acquisition of competencies and skills necessary in the 21st century· Solutions were proposed to address the lack of connectivity in rural areas, such as the use of offline educational platforms, printed materials, portable devices preloaded with educational content, educational radio and television programs, classrooms equipped with the Internet, and alliances with telecommunications companies·